Amalan penamaan harta orang islam di Malaysia: Satu tinjauan ringkas menurut syariah islamiah - Md. Yazid Ahmad,; Ibnor Azli Ibrahim, (Universiti Kebangsaan Malaysia, 2002)
This article discusses the position of nominee property among the muslims in Malaysia from the Islamic perspective. For that reason, the analysis of the nominee property is carried out as it is hibah property, wasiat property and property which is subjected to wasiat regulation as a wasi (trustee). The study is based on library methodology in which relevant books in fiqh, law and cases are collected and analyzed. According to Islamic law, the study shows that the nominee property should be categorised as a property which is subjected to wasiat regulation i.e the nominee act as a wasi (trustee) to the share of inheritance which should be divided to the legitimate heirs